Malaysian Students and the Japanese Writing System - Kampmark, Karl J. (Journal of Modern Languages, 2017)
This paper attempts to consider the particular problems of the Chinese students face in learning Japanese language, specifically in learning to write Japanese at the University of Malaya. The study mentions that more than ninety percent of the students of Japanese at the University of Malaya are ethnic Chinese. It also compares the differences between Japanese language and Chinese language.